Electrocatalytic Oxygen Reduction Reaction on Iron Phthalocyanine-Modified Carbide-Derived Carbon/Carbon Nanotube Composite Electrocatalysts - Zagal-Moya, J; Zagal-Moya, J (Elsevier Ltd, 2020)
We have investigated the electrocatalytic activity of pyrolysed iron phthalocyanine (FePc) modified carbide-derived carbon/multi-walled carbon nanotube (CDC/CNT) composite materials for the electroreduction of O2. For comparison, FePc supported on Ketjenblack (KB/FePc) and heat-treated at 800 °C was also investigated. All materials containing a higher weight ratio of the CNTs exhibit higher electrocatalytic activity for oxygen reduction reaction (ORR) in both alkaline and acidic media. The surface morphology, structure, elemental composition and porosity of the electrocatalysts were studied with scanning electron microscopy, X-ray diffraction analysis, X-ray photoelectron spectroscopy, microwave plasma atomic emission spectroscopy and N2 adsorption-desorption analysis. Anion exchange membrane fuel cell (AEMFC) tests were performed with the most active FePc modified CDC/CNT and KB/FePc catalysts. Excellent AEMFC performance was observed using these FePc derived cathode catalysts (maximum power density of 186 mW cm−2 for KB/FePc). © 2019 Elsevier Ltd